2019
DOI: 10.1148/radiol.2018180230
|View full text |Cite
|
Sign up to set email alerts
|

Four-dimensional Flow MRI as a Marker for Risk Stratification of Gastroesophageal Varices in Patients with Liver Cirrhosis

Abstract: To assess the feasibility of four-dimensional (4D) flow MRI as a noninvasive imaging marker for stratifying the risk of variceal bleeding in patients with liver cirrhosis. Materials and Methods: This study recruited participants scheduled for both liver MRI and gastroesophageal endoscopy. Risk of variceal bleeding was assessed at endoscopy by using a three-point scale: no varices, low risk, and high risk requiring treatment. Fourdimensional flow MRI was used to create angiograms for evaluating visibility of va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…57,58 Moreover, a small proof-of-concept study using four-dimensional (4D) flow MRI linked azygos flow to high-risk varices. 59 Another proof-of-concept study (58% CTP stage B/C; 67% CSPH) used PC-MRI to assess total liver blood flow by subtracting infra-from suprahepatic caval blood flow in 12 patients with ACLD. Furthermore, the authors also measured portal venous blood flow and calculated hepatic artery fraction (i.e., a measure of the increased arterial perfusion/splanchnic vasodilatation in patients with ACLD), the latter showing a direct correlation of moderate strength (Pearson's r ¼ 0.78) with HVPG.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…57,58 Moreover, a small proof-of-concept study using four-dimensional (4D) flow MRI linked azygos flow to high-risk varices. 59 Another proof-of-concept study (58% CTP stage B/C; 67% CSPH) used PC-MRI to assess total liver blood flow by subtracting infra-from suprahepatic caval blood flow in 12 patients with ACLD. Furthermore, the authors also measured portal venous blood flow and calculated hepatic artery fraction (i.e., a measure of the increased arterial perfusion/splanchnic vasodilatation in patients with ACLD), the latter showing a direct correlation of moderate strength (Pearson's r ¼ 0.78) with HVPG.…”
Section: Magnetic Resonancementioning
confidence: 99%
“…Regarding portal-hypertension-related diseases, IR treatments raise serious post-therapeutic concerns that include the emergence of ascites, deterioration of other varices, portal thrombosis, and liver failure [16,17]. Although each modality has drawbacks, recent US and 4D flow MRI studies have revealed the relationship between portal flow and the deterioration of gastroenteric varices and liver function [2,[18][19][20]. IR treatments can alter the flow dynamics of the portal circulation between pre-and post-therapy, resulting in changed liver function [18,20].…”
Section: Introductionmentioning
confidence: 99%
“…Phase‐contrast MRI with three‐directional velocity encoding and cardiac gating (4D flow) allows for time‐resolved quantification of blood flow across any plane, definable before or after the acquisition, within the imaging volume 13–22 . Major challenges to routine use in abdominal imaging include long scan duration and artifact from respiratory and cardiac motion.…”
mentioning
confidence: 99%